Suspensor and Early Embryo of Pinus - Buchholz, John Theodore (Botanical gazette (Chicago, Ill.), 1918)
1. A special technique for dissecting ovules, staining and mounting the embryos, and an improved method of staining embryos in serial sections have been described in detail. 2. The corrosion cavity results from an enzyme, which may be secreted by the unfertilized eggs as well as the embryo. 3. Two forms of polyembryony must be recognized in gymnosperms, namely, cleavage polyembryony and the polyembryony due to pleurality of archegonia. In Pinus one usually finds both types associated in the same ovule, and cleavage polyembryony always occurs in the several species of Pinus that were investigated. It is probably a constant feature of this genus. 4. The rosette consists of a group of embryo initials which usually produce embryos. Rosette embryos, like 3 of the 4 primary embryos, are always aborted. 5. Each embryo of a system may be traced back to an initial cell, one of the first completely walled cells of the proembryo. The8 embryos formed by the cleavage of the egg are therefore definitely organized from the time of the last free nuclear division. 6. A further splitting of one of these 8 embryos into "twins" was not found to occur in Pinus. In rare cases 2 matured embryos were found in an ovule, but they were very unequal and due simply to the incomplete dominance of a single embryo. 7. The early embryo develops by means of an apical cell which exists from the time the first walls appear in the proembryo. This apical cell persists for a considerable period, being still recognizable in embryos of 500-700 cells. 8. The apical cell represents a primitive fern character, which is recapitulated in the embryogeny of Pinus. 9. Less than 4 primary embryos per archegonium may be produced in case one of the embryo initials, or the early apical cell,disorganizes. 10. The suspensor is formed by the elongation of cells in the basal portion of the embryo, a process that begins with the elongation of the first apical cell segment and continues until the maturity of the embryo. 11. Suspensor cells or embryonal tubes never divide after elongation, but rosette cells may elongate and later divide in forming the rosette embryos, showing their greater potentialities and their distinctness from the suspensor cells which they resemble. 12. Considerable variation occurs in the first secondary suspensor divisions, also in the time of appearance of the first oblique walls formed by the apical cell; both are doubtless related to the time of separation of the embryos. 13. Cleavage polyembryony is a primitive character which Pinus, Sciadopitys, Actinostrobus, and doubtless other genera have retained. Ephedra has also retained it in a modified form, and this definitely associates Gnetales with the Coniferales rather than the cycads. 14. The other evolutionary lines suggested in the discussion likewise assign a primitive position to Pinus, so that this ancient type seems to be genetic to several conifer lines. 15. The body regions of the later embryo, so far as they have been determined, appear in the following order: plerome tip of root, periblem and root cap, stem tip, and cotyledons. 16. There is a distinct tendency in P. Banksiana toward a reduction in the number of cotyledons, attested by the fact that 2 primordia have been found to form 1 broad cotyledon. This suggests that the dicotyledonous condition has been derived from the polycotyledonous condition through cotyledonary fusions. 17. Cotyledonary tubes are the result of past cotyledonary fusions, and are found in embryos between the primitive polycotyledons and dicotyledons. 18. The zygomorphic feature of a monocotyledonous embryo is foreshadowed in the embryo of Pinus.